Drone-based composite risk mapping reveals vegetation–shade interaction and housing typology as key determinants of Aedes habitat risk - Mahfodz, Zulfadli; Naba, Agus; Isawasan, Pradeep; Osman, Mohd Azuraidi; Che Dom, Nazri (Nature Research, 2026)
Persistent dengue transmission in tropical cities reflects a complex interplay between environmental microclimates and urban housing structure that supports Aedes mosquito breeding. This study applies drone-based microhabitat risk mapping integrated with a biologically defined Composite Risk Index (CRI) to quantify fine-scale environmental drivers of Aedes habitat risk across distinct residential typologies in Sect. 24, Shah Alam, Malaysia. High-resolution RGB imagery obtained using a DJI Phantom 4 Pro was processed to derive the Brightness Index (BI) as a proxy for shade intensity and the Excess Green Index (ExG) as an indicator of vegetation density. These indices were integrated a priori into a CRI to operationalise known ecological conditions favourable for Aedes. Spatial analysis revealed a consistent risk gradient, with terrace housing exhibiting higher Composite Risk Index (CRI) values than flat complexes (low-density terrace (Teres D) > dense terrace (Teres B) > medium-rise (Flat H) > high-rise (Flat B)), demonstrating that housing typology modulates the spatial expression of microhabitat risk rather than vegetation presence alone. Model calibration showed high predictive agreement (R² = 0.91), with the top 20% of CRI-ranked pixels capturing 65% of observed breeding-prone zones, indicating strong spatial discriminative performance. These findings highlight that vegetation–shade coupling, expressed through housing morphology, governs Aedes habitat persistence and that drone-based microclimate mapping provides a precision surveillance tool for spatially targeted dengue control.